(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Based on intermediate testimonies, it is known that Cvijeta Zuzoric inspired many Renaissance poets from Dubrovnik and Italy. According to the perceptions of her contemporaries, she was the embodiment of physical beauty and spiritual perfection. At the same time, she gave a unique tone to the intellectual circles of Dubrovnik in the 16th century. As a result, a special cult of Cvijeta Zuzoric, which outgrew her individuality and made her into a Renaissance symbol of this region, was formed after some time.